The role of pelvic lymph node dissection during radical prostatectomy in patients with Gleason 6 intermediate-risk prostate cancer - Mandel, Philipp; Kriegmair, Maximilian (Urology, 2016)
Objective - To analyze the benefit of pelvic lymph node dissection (PLND) in patients with biopsy Gleason grade ≤ 6, cT ≤ 2b, and prostate-specific antigen (PSA) 10-20 ng/mL (main study cohort), as the indication for PLND during radical prostatectomy remains uncertain in patients with nonhigh-risk tumors. - Materials and Methods - The main study cohort included 1383 patients with low intermediate-risk cancer undergoing radical prostatectomy with or without PLND between 1994 and 2013. Positive lymph node (LN) rates were reported and compared to patients with higher (≥20 ng/mL; n = 314) and lower (<10 ng/mL; n = 6861) PSA. Oncological outcome was assessed by Cox regressions in patients with a minimum follow-up of 5years. - Results - In the main study cohort (PSA 10-20 ng/mL), PLND was performed in 867 (62.7%) patients with a median number of removed LNs of 11 (interquartile range 16-6). Positive LNs were detected in 3.3% of these patients. Compared to the main study cohort, patients with preoperatively higher PSA ≥ 20 ng/mL (or lower PSA < 10 ng/ml) underwent PLND in 83.8% (32.7%) of the cases, with 8.0% (1.8%) showing positive LNs. Median follow-up in the main study cohort was 84.5 months. Biochemical recurrence (BCR) occurred in 20.6% of these men. The 5-year and 10-year BCR-free survival rates were 82.2% and 75.6% for those with PLND, and 83.4% and 75.8% for patients without PLND. PLND was not a significant factor influencing BCR-free, metastasis-free, or cancer-specific survival in the main study cohort. - Conclusion - Positive LNs are rare in patients with Gleason grade ≤ 6, cT ≤ 2b, and PSA 10-20 ng/mL. Performing PLND had no statistical influence on oncologic outcome and therefore should be decided upon on an individual basis.